Prevalence and factors associated with fear of COVID-19 in military personnel during the second epidemic wave in Peru - Valladares-Garrido, Danai; Dominguez-Troncos, Helena; Picón-Reátegui, Cinthia Karina; Valdiviezo-Morales, Christopher; Vera-Ponce, Víctor J.; Failoc-Rojas, Virgilio E.; Pereira-Victorio, César Johan; León-Figueroa, Darwin A.; Valladares-Garrido, Mario J. (Frontiers in Psychiatry, 2024)
During the COVID-19 pandemic, the mounting workload and heightened stress may contribute to exacerbated mental health challenges, including an increased fear of COVID-19, among military personnel. Despite the potential influence of these factors, there remains a scarcity of studies addressing mental health issues, particularly the fear of COVID-19, within this specific population. We aimed to determine the prevalence and factors associated with fear of COVID-19 among military members. A cross-sectional study was conducted between November 2 and 9, 2021, during the second wave of the COVID-19 pandemic in the Lambayeque region, Peru. The outcome variable was fear of COVID-19, assessed using the Fear of COVID-19 Scale. The association with resilience (Connor-Davidson Resilience Scale, abbreviated as CD-RISC), food insecurity (Household Food Insecurity Access Scale, abbreviated as HFIAS), physical activity (International Physical Activity Questionnaire-Short Form, abbreviated as IPAQ-S), eating disorder (Eating Attitudes Test-26, abbreviated as EAT-26), and other sociodemographic variables was assessed. Among the 525 participants, the median age was 22, 95.8% were male, and 19.2% experienced fear of COVID-19. A higher prevalence of fear of COVID-19 was associated with age (PR=1.03; 95% CI: 1.01-1.06), religion (PR=2.05; 95% CI: 1.04-4.05), eating disorder (PR=2.95; 95% CI: 1.99-4.36), and having a relative with mental disorder (PR=2.13; 95% CI: 1.09-4.17). Overweight (PR=0.58; 95% CI: 0.37-0.90) and a high level of resilience (PR=0.63; 95% CI: 0.43-0.93) were associated with a lower prevalence of fear of COVID-19. Two out of ten military personnel were afraid of COVID-19. Our results highlight the need for targeted interventions addressing the factors contributing to fear of COVID-19 among military personnel, emphasizing the significance of mental health support and preventive measures within this specific population..